2021
DOI: 10.1039/d1nj01440d
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented interplay of antiferro- and ferromagnetic exchange interactions through intermolecular hydrogen bonds in mononuclear Cu(ii) complexes

Abstract: Copper(II) coordination compounds with the condensation product of the diacetylmonoxime and 2-hydrazino-4,6-dimethylpirimidine (H2L) with composition [Сu(Н2L)Br2]·Н2О (I) and [Сu(Н2L)Cl2] (II) were synthesized. Molecular structures of the compounds were established with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In earlier reports, it has been observed that the transition metal complexes, in particular Cu( ii ) complexes, show effective exchange interactions through intra- or intermolecular hydrogen bonding. 24 In complexes 2 and 3 , the coordinated water molecule forms a strong hydrogen bond with the O atoms coordinated to the Cu( ii ) ion. Therefore, we have considered two exchange interactions between Cu( ii ) and Ln( iii ) centers during the simulations as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In earlier reports, it has been observed that the transition metal complexes, in particular Cu( ii ) complexes, show effective exchange interactions through intra- or intermolecular hydrogen bonding. 24 In complexes 2 and 3 , the coordinated water molecule forms a strong hydrogen bond with the O atoms coordinated to the Cu( ii ) ion. Therefore, we have considered two exchange interactions between Cu( ii ) and Ln( iii ) centers during the simulations as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…63 However, it could not be ruled out that the values of J may also be effected by other factors since copper-nitroxide systems are characterized by the sensitivity of exchange interactions to geometry and the electronic structure. 67 To clarify the dissociation ability of complex 3 in solution, a reaction with pyrazolone 4 was carried out (Scheme 3). The choice of substrate is based on a previously known transformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As noted above, the difference in the sign of magnetic interactions correlates with the sign of the spin population on the coordinating oxygen atom; namely, the positive sign of the spin population leads to an antiferromagnetic exchange interaction, and the negative sign leads to a ferromagnetic one (McConnell I mechanism) . However, it could not be ruled out that the values of J may also be effected by other factors since copper-nitroxide systems are characterized by the sensitivity of exchange interactions to geometry and the electronic structure …”
Section: Resultsmentioning
confidence: 99%